Hubungan Kadar Vitamin D dan Kadar C-Reactive Protein dengan Klinis Pasien Coronavirus Disease 2019 - Berhandus, Catrien; Ongkowijaya, Jeffrey A.; Pandelaki, Karel (Universitas Sam Ratulangi, 2021)
Abstract: COVID-19 patients could experience many respiratory symptoms accompanied with increased inflammatory markers, such as C-reactive protein (CRP). Vitamin D is known to have a positive effect on immune system by decreasing inflammatory process. This study was aimed to evaluate the relationship between vitamin D and CRP concentration and clinical severity, and the correlation between vitamin D concentration and CRP concentration in COVID-19 patients. This was an observational and analytical study with a cross-sectional design conducted at Prof. dr. R. D. Kandou hospital. A total of 40 subjects with COVID-19 were included. Clinical severity was classified into moderate and severe. All subjects underwent vitamin D and CRP concentration examination. The results showed that there was a significant relationship between vitamin D level and clinical severity of patients with COVID-19 (p=0.0001). There was a significant relationship between CRP level and clinical severity of patients with COVID-19 (p=0.0001). Moreover, there was a negative correlation between vitamin D concentration and CRP concentration (r=-0.49, p=0.001). In conclusion, vitamin D insufficiency or deficiency is related to CRP increament and clinical severity of patients with COVID-19.Keywords: coronavirus disease 2019, vitamin D, C-reactive protein (CRP), clinical severityAbstrak: Penderita COVID-19 mengalami berbagai gejala pernapasan disertai dengan pening-katan beberapa penanda inflamasi, salah satunya C-reactive protein (CRP). Vitamin D diketahui memiliki efek positif terhadap sistem imun tubuh dengan cara meredam proses inflamasi berlebihan. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara kadar vitamin D dan kadar CRP dengan klinis COVID-19, dan korelasi antara kadar vitamin D dengan kadar CRP. Jenis penelitian ini ialah studi analitik observasional dengan desain potong lintang yang dilakukan di RSUP Prof. dr. R. D. Kandou. Total sampel sebanyak 40 pasien dengan diagnosis COVID-19. Gejala klinis pasien dibagi menjadi sedang dan berat. Pemeriksaan kadar vitamin D dan kadar CRP dilakukan pada seluruh sampel. Hasil penelitian mendapatkan hubungan bermakna antara kadar vitamin D dengan klinis pasien COVID-19 (p=0,0001), dan antara kadar CRP dengan klinis pasien COVID-19 (p=0,0001). Terdapat korelasi negatif antara kadar vitamin D dengan kadar CRP (r=-0,49, p=0,001). Simpulan penelitian ini ialah insufisiensi atau defisiensi vitamin D berhubungan dengan peningkatan CRP dan klinis pasien COVID-19.Kata kunci: coronavirus disease 2019, vitamin D, C-reactive protein (CRP), gejala klinis